Public Requitals: Corrective, Retributive, and Distributive Justice - Kuklin, Bailey (2018)
The currently predominant view of public requitals for criminal behavior draws on the deontic guidance provided rather sketchily by Kant’s writings. He offers a broad, formal framework for the mandate to respect others and punish those who criminally violate the mandate. As ethical beings, people have the duty to avoid invading the autonomy space of others that is delineated by maxims designed to reasonably and fairly balance everyone’s equal liberty and security interests. Once society settles on a complete and coherent set of maxims that determines the reach of one’s autonomy space, it must then turn to maxims that address the requital repercussions for invasions of this space. In the private realm, our legal regime looks to corrective justice for guidance. In the public, criminal realm we turn to... Well, here is where a deep debate resides. Might we think of punishment as corrective justice writ large? This does not seem promising since our intuitions and traditions emphasize the blameworthiness of the criminal autonomy invader, which corrective justice downplays. Instead, should we turn to conceptions of retribution, as Kant asserts? If so, what are the parameters of retribution? While this is more promising, I believe the prominent role of blameworthiness in our judgments of apt punishment are best situated by conceptions of distributive justice. Defending and developing this position is the primary burden of this Article. After explicating the key elements of autonomy space and requitals for its invasion, including dignity, respect, responsibility, consent, harm, wrongful harm, and especially blameworthiness, I turn to the process by which these elements may be integrated and implemented in a just penal regime centered on distributive justice